Examination of the knee - Tang,QO; Gupte,CM (2016)
The art of clinical examination is often forgotten with the advent of increasingly precise imaging modalities but in fact remains the most powerful tool in the surgeon’s armamentarium and is at the heart of the patient- clinician relationship. A clear examination sequence forms a fundamental tool for the diagnosis and correct treatment of knee pathology. Whilst this is important, the advanced examiner together with the history will tailor a specific exam series depending on the suspected pathology. In general, there are three broad series: one for patellofemoral/extensor mechanism pathologies; one for meniscal and chondral (articular) lesions; and one for instability. This chapter will provide an overview of advanced physical examination of the knee and outlines the most commonly used tests. Images and detailed descriptions will provide the reader with a thorough understanding of hand positions and identifying a positive sign.